ANALISA PENGARUH PERUBAHAN SUDUT PENGAPIAN DISTRIBUTOR TOYOTA KIJANG 4K TERHADAP UNJUK KERJA MESIN - Muhammad Firman; Muhammad Irfansyah; Risko Agung Prasetyo (AL-JAZARI JOURNAL SCIENTIFIC OF MECHANICAL ENGINEERING, 2017)
Motor vehicles are a means of transport for which the engine from the beginning, both for two-wheel vehicles, as well as for four-wheeled vehicles. The automotive fuel is a machine that is used as a transport mover soon. The automotive fuel is an engine type conversion that converts the chemical energy of the fuel into mechanical energy through the combustion process in the combustion chamber.This research was conducted using the method or approach theoretically and experimentally. The vehicles to be used in this research is the engine of the Toyota Kijang 4K using premium fuel stations, test equipment used in this study is a dynamometer with changes 5° ignition angle, 8°, 10°, 12°, 15° with the variation of the rotation of the motor 1000, 1500, 2000, 3000 rpm. Regarding the position to carry out research at the Center for Professional Training (BLK) Banjarbaru in JL.IR PM Noor 1.5 Km River Ulin Banjarbaru South Kalimantan.Based on the results of the study of variations of the performance of the engine ignition distributor concluded that: the effective torque of 108,85381 Nm, which is contained in the ignition angle 12° with the motor rotation of 3000 rpm, the effective power contained in the corner Ignition of rotation of 3000 rpm 12° reach 34,18021 (Kw) and efektir pressure contained in the ignition angle 12° at 3000 rpm round reached 6387,235(kg/cm²). The increase in torque due to rotation higher up to reach the maximum price, this is because the amount of fuel in the combustion chamber and the greater the influence of the right letikan sparks from the spark plug so that the energy generated through process burn largest.Keywords: ignition angle, torque, Brake Horse Power (BHP), Brake Mean Pressure (BMEP)